Pengaruh Board Structure terhadap Firm Performance melalui Intellectual Capital Pada Perusahaan Sektor Barang Konsumsi, Perdagangan, Jasa dan Investasi Pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Gabriella Karuniajaya Hartono; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the relationship of board structure towards firm performance with intellectual capital as an intervening variable. The sample used in this study comprised of corporations within consumer goods sector (cigarette, pharmacy, cosmetic, household necessities, household-appliance, food and beverages sub-sectors) trade, service, and investment sectors (whole-sale and retail sub-sectors) listed in Indonesia Stock Exchange (IDX) during 2010 to 2015. The data collected from the 2010-2015 annual reports with a total of 295 observed reports. The data is analyzed by using WarpPLS 5.0 to describe the relationship among the variables. Board structure was measured from board size, board composition, and board meeting, intellectual capital was measured using value added intellectual capital, and the last return on asset was used as a measurement for firm performance. The results showed that there was significant influence of board structure towards intellectual capital, board structure towards firm performance and intellectual capital towards firm performance.